Bilayer Graphene: From Stacking Order to Growth Mechanisms. Issue 3 (3rd January 2020) - Guan, Ran; Yuan, Aiheng; Luo, Birong
Abstract : Due to the unique bandgap tunability of bilayer graphene, the preparation of large‐sized bilayer graphene has attracted a wide range of attention. Herein, the preparation of bilayer graphene, from stacking order to growth mechanism, is reviewed, and the chemical vapor deposition (CVD) of AB‐stacked bilayer graphene on copper substrate is emphasized. Various methods and growth strategies to synthesize bilayer graphene and the corresponding growth mechanisms are discussed. Mechanisms of layer‐by‐layer growth, the hydrogen passivation of graphene edges for the formation of bilayers, and carbon atoms penetrating through a copper wall for bilayer growth are included and highlighted for a better understanding of controlling bilayer graphene uniformity and forming its stacking order. Finally, the remaining challenges and the potential development of CVD‐controlled growth of bilayer graphene are outlined. Abstract : The stacking order, characterization, and chemical vapor deposition (CVD) growth mechanisms of bilayer graphene are reviewed. With the insights and understanding provided by various CVD methods and strategies, preparation of bilayer graphene with controlled stacks and large area is expected to facilitate applications.